2011
DOI: 10.1021/jp2048713
|View full text |Cite
|
Sign up to set email alerts
|

Photoinduced Degradation Studies of Organic Solar Cell Materials Using Kelvin Probe Force and Conductive Scanning Force Microscopy

Abstract: We investigated the photoinduced changes in the surface potential and conductivity for locally degraded active layers of organic solar cell materials using electrical modes of scanning force microscopy. Samples were degraded under different partial pressures of oxygen and humidity in the presence of light. Degraded and nondegraded areas were investigated by Kelvin Probe Force Microscopy (KPFM) and conductive scanning force microscopy (cSFM). The analysis allowed us to quantify the extent of degradation and com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 37 publications
0
20
0
Order By: Relevance
“…The issue of degradation in polymer solar cells is complex owing to the plethora of degradation pathways that occur within the many layers comprising the device architecture. Significant literature can be found on this problem, including some excellent reviews and the identification of numerous factors such as oxygen, water, light, heat and mechanical stresses as some of the crucial degradation triggers. The decline in photovoltaic performance with time is largely due to the combined action of interrelated parallel mechanisms at different locations of the device, with specific kinetics.…”
Section: Example Employment Of Photo‐celiv and Tof – Following Degradmentioning
confidence: 99%
“…The issue of degradation in polymer solar cells is complex owing to the plethora of degradation pathways that occur within the many layers comprising the device architecture. Significant literature can be found on this problem, including some excellent reviews and the identification of numerous factors such as oxygen, water, light, heat and mechanical stresses as some of the crucial degradation triggers. The decline in photovoltaic performance with time is largely due to the combined action of interrelated parallel mechanisms at different locations of the device, with specific kinetics.…”
Section: Example Employment Of Photo‐celiv and Tof – Following Degradmentioning
confidence: 99%
“…19,20 Particularly, conducting AFM has already been introduced to study the degradation of active layer from conjugated polymer and PCBM blend by varying environmental condition. 21 In addition to the environmental elements, the presence of solvent vapors during fabrication process steps or even the way of characterizations done can affect the device performance considerably. But it is already reported that the long-term stability is an issue when using PEDOT:PSS as HTL due to the instability of the strongly hygroscopic counterpart poly-(styrene sulfonate) which dissociates under the inuence of moisture in the air.…”
Section: Introductionmentioning
confidence: 99%
“…The design and development of renewable energy sources using organic solar cells (OSC) have attracted considerable interest in recent years due to increasing energy demand. [1][2][3][4][5][6][7] Owing to their large surface areas and porous structures, metal organic frameworks (MOF) and covalent organic frameworks (COF) have been the subject of research in the areas of gas storage and catalysis. [8][9][10][11][12] Quantum chemical calculations have been used to understand not only the nature of MOFs/COFs (both in the ground and excited states) but also the character of their bands.…”
Section: Introductionmentioning
confidence: 99%